Deformation Styles and Multi-Stage Evolution History of a Large Intraplate Strike-Slip Fault System in a Paleozoic Superimposed Basin: A Case Study From the Tarim Basin, NW China - Neng, Yuan; Li, Yong; Qi, Jiafu; Ma, Xiao; Zuo, Liang; Chen, Ping (Frontiers in Earth Science, 2022)
The complex deformation styles of large intraplate strike-slip fault systems in the multi-stage superimposed basin are hot topics worldwide. This paper proposes structural models and evolution processes for such strike-slip fault systems in the Tarim Basin based on high-resolution 3D seismic data, and deep wells. Our analyses reveal that: Strike-slip fault in the Tarim Basin formed with different structural styles in 5 tectonic layers from the Sinian to the Permian that accompanies the Sinian rift systems and uplift, the Lower-middle Cambrian reversed faults and salt tectonics, the Ordovician fault karst systems, the Silurian to the Carboniferous en echelon transtensional faults and the Permian volcanic structures. Influenced by the multi-tectonic layers, complex evolution history, the strike-slip faults performed as multi-layer flower structures and various fault types. The evolution history of paleo uplifts also influenced the distribution characteristics of Strike-slip fault such as X-, diamond-, V-shapes in the Tabei uplift and T-shapes in the Tazhong Uplift. The strike-slip faults formed in late Cambrian stage were associated with unconformities, inverted structures, and growth strata in deep layers. The different tectonic evolution model of Tabei and Tazhong uplift was built which shows pre-existing structures, the lithological combination from the rift basin to the ocean basin, and the change of regional tectonic stress from Cambrian to Permian are controlling factors of the strike-slip fault system. These models provide a new interpretation method for intraplate strike-slip fault systems worldwide.